Predisposing, Supporting and Driving Factors for Utilization of Adolescent Care Health Services in South Kuta - Rini Winangsih; Desak Putu Yuli Kurniati; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: Targetted adolescent health services (PKPR) at the South Kuta Health Center have been offered since 2007. However, these are rarely accessed (less than 5 visits per month) whereas adolescent health incidents/concerns such as abortion, HIV/AIDS and drug use are reported to increase. This study aimed to determine the predisposition, supporting and reinforcing factors of PKPR utilization. Methods: The study was qualitative and conducted among 27 students in four sessions of focus group discussions, as well as indepth interviews with four key informants. Data collected consisted of knowledge, attitudes and views of participants on PKPR facilities. Thematic analysis was conducted to identify predisposition, supporting and reinforcing PKPR utilization factors. Results: The study participants intimated that their knowledge about PKPR was low, although they recognised the benefits of such service. They also acknowledged that the quality of facilities/infrastructure were poor, the IEC materials were interesting but the deliverance was unclear and the attitude of providers was unfriendly. Funds, inappropriate clinic hours and labor provided were minimal. Schools, health centers and the government health office strongly supported PKPR activities and the role of peer counselors. School health programs also encouraged students to take advantage of PKPR. Conclusion: Local schools, health centers and the government health office were supportive of PKPR activities, however the student’s knowledge about PKPR was low because coverage of PKPR was very limited.